The protection of computer programs in Turkish law on intellectual and artistic works - Şenol, A. Nilay (My University, 2004)
In this thesis, the legal protection of computer programs in Turkish Law on Intellectual and Artistic Works has been studied. The aim of this research work is to point out the importance of legal protection of computer programs. Turkey has amended the Law on Intellectual and Artistic Works in the light of European Union Directive on legal protection of computer programs. The topic is examined in three chapters. First of all, the concept of computer programs and elements of computer programs are defined. The theories on legal character of computer programs are examined and following this the different legal frameworks for the protection of computer programs are examined pointing both the advantages and disadvantages of all. In the second chapter, the intellectual protection under Turkish Law on Intellectual and Artistic Works in comparison with European Union Directive is examined. Finally, the civil actions are pointed out giving examples from court decisions. Consequently, the opinion that has been reached to is that the right on a computer program is an intellectual right. Furthermore, although it is protected under copyright law, sui generis protection has to be taken into consideration.

Çalışmamızda bilgisayar programlarının Türk Fikir ve Sanat Eserlerine göre korunması incelenmiştir. Bu araştırmanın amacı bilgisayar programlarının hukuki korunmasının önemine değinmektir. Türkiye de taraf olduğu uluslararası antlaşmalar ve Gümrük Birliği anlaşması gereğince bilgisayar programlarını Fikir ve Sanat Eserleri Kanununda korumaya almıştır. Konu, üç bölümde incelenmiştir. İlk olarak, bilgisayar ve bilgisayar programlarının unsurları açıklanmıştır. Bilgisayar programları üzerindeki hakların hukuki niteliğini açıklayan teorilere değinilmiş ve korumanın hangi hukuk dalı altında yapılması gerektiğine dair gelişmeler açıklanmıştır. İkinci bölümde, Türk Fikir ve Sanat Eserleri Kanununa göre koruma, Avrupa Birliği yönergesiyle karşılaştırmalı olarak incelenmiştir. Son olarak, kanundan doğan hukuk davaları ve diğer hükümlere değinilmiştir. Fikir ve Sanat Eserleri Kanununda, mali ve manevi hakların ihlali halinde öngörülen hukuk davaları tecavüzün kaldırılması davası, tecavüzün önlenmesi davası ve tazminat davalarıdır.
Keywords: Avrupa Birliği_Hukuk